Spatial Sense in the Secondary Mathematics Curriculum in Costa Rica - Monge Madriz, Carlos (2026)
Spatial sense is an essential capacity for geometric understanding and the development of mathematical thinking. In recent years, it has gained increasing relevance in mathematics curricula, as its role in the comprehensive formation of geometric thinking has been recognized. This article analyzes the Costa Rican secondary school mathematics curriculum from the perspective of spatial sense, with the purpose of identifying how its dimensions are integrated and what emphasis they receive across educational levels. In 2024, a qualitative, documentary, and descriptive study was conducted through content analysis of the learning skills established in the official Mathematics curriculum of the Costa Rican Ministry of Public Education. The units of analysis corresponded to these learning skills, coded according to two main components of spatial sense: the management of geometric concepts and visualization skills. The findings reveal an uneven distribution of spatial sense dimensions in the curriculum. Learning skills related to the properties of shapes and figures and to figure–ground perception predominate, whereas those linked to locations and movements or the conservation of perception are less represented. The Costa Rican curriculum acknowledges spatial sense as a goal of geometric learning, although its implementation appears fragmented. It is recommended to strengthen the dynamic and visual dimensions of geometry to promote a more balanced development of spatial sense and to guide future curricular revisions and teaching practices.